Stability of triaxial weave fabric composites employing finite element model with homogenized constitutive relation - Rasin, Norhidayah (2013)
This study examines numerically the uniaxial stability of triaxial weave fabric (TWF) composites employing finite element (FE) model with homogenized constitutive relation. TWF, which presents high specific-strength and stiffness due to its porous and lightweight properties, was previously modelled using solid elements or plybased approach, and thus making computation considerably complex and timeconsuming. To circumvent these issues, the current FE formulation is of geometrical nonlinearity employing Newton-Rhapson method where TWF unit cell is treated as a standalone non-conforming composite plate element making use of the homogenized ABD stiffness matrix, where Aij, Bij, and Dij indicate the extensional, coupling, and bending stiffness, respectively in which degree of freedom has been greatly reduced. By means of Matlab program, the currently formulated model has demonstrated good agreement with existing numerical and experimental results from literature in terms of elastic properties. For the buckling analysis, four types of boundary conditions are explored: fully simply supported, fully-clamped, free-simply supported and freeclamped. High dependencies of post-buckling patterns of compression load against both maximum and minimum deflections on numerous aspect ratios from 0.25 to 5 are observed in TWF, from which a characteristic equation has been defined for practical convenience before the occurrence of post-buckling. Such equation is described on the basis of the critical buckling load, Nmax, and stiffness factor, S, the best characterization of which is expressed in a logarithmic manner. The study has recognized that the buckling characteristics correlate directly to TWF’s aspect ratios and level of rigidity imposed through the boundary conditions.